Prediction of outcome by lymph node ratio in patients with parotid gland cancer. (30th May 2016) - Meyer, M.F.; Kreppel, M.; Meinrath, J.; Grünewald, I.; Stenner, M.; Drebber, U.; Quaas, A.; Odenthal, M.; Semrau, R.; Huebbers, C.U.; Zöller, J.; Huettenbrink, K‐B.; et al.
Abstract : Objective: Lymph node ratio (LNR) has been shown to be an independent predictor of recurrence risk and survival in different entities of carcinoma. Methods: In this retrospective chart review, 128 patients with parotid gland cancer (PGC) subsequently treated by primary surgery were included. About 64% ( n  = 82) of these patients were additionally treated with adjuvant radiotherapy. Five‐year overall survival rates were determined by subgroups based on LNR value. Results: Lymph node ratio was found to be significantly associated with overall survival rate ( P  <   0.001). Using univariate analyses, pathological tumour‐node‐metastasis (TNM)‐stage, UICC‐stage grouping and extracapsular spread were found to be significant predictors of overall survival ( P  < 0.001). However, with a multivariate analyses, LNR remained the only independent predictor of overall survival ( P  = 0.043). Conclusions: After surgery for PGC, evaluation of the neck using LNR was found to reliably stratify the overall survival rate.